2021
DOI: 10.2166/wst.2021.272
|View full text |Cite
|
Sign up to set email alerts
|

Migration and transformation of heavy metals during the microwave-assisted thermal hydrolysis of sewage sludge

Abstract: The migration, transformation and ecological risk of heavy metals (Cr, As, Ni, Cu, Zn, Cd and Pb) in the sewage sludge during the microwave-assisted thermal hydrolysis process were investigated under different temperatures (80 °C, 100 °C, 120 °C, 140 °C, and 160 °C). The potential relationship between the bio-availability of heavy metals and the variables of microwave treatment, including pH, ammonium-nitrogen, soluble chemical oxygen demand, pH, soluble protein, soluble polysaccharide and volatile solid, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Previous study pointed out that the migration of heavy metals between solid-liquid phase mainly depended on the temperature. The percentage of all heavy metals (except Cu) in mobile (acid-soluble/exchangeable and reducible) forms decreased after microwave-assisted thermal hydrolysis treatment (Qiu et al 2021). The general conclusion was in line with the present study.…”
Section: Total Heavy Metal Contentsupporting
confidence: 92%
“…Previous study pointed out that the migration of heavy metals between solid-liquid phase mainly depended on the temperature. The percentage of all heavy metals (except Cu) in mobile (acid-soluble/exchangeable and reducible) forms decreased after microwave-assisted thermal hydrolysis treatment (Qiu et al 2021). The general conclusion was in line with the present study.…”
Section: Total Heavy Metal Contentsupporting
confidence: 92%
“…Previous studies found that a great proportion of heavy metals remained in biochar after pyrolysis treatment, but partial heavy metals could be transferred to the liquid product (bio-oil) or gas phase (Lu et al 2015;Qiu et al 2021), resulting in the content reduction of Ni. Meanwhile, the concentrations of Cr in BC500, BC600, and BC700 increased by 20.35%, 15.24% and 6.95%, respectively, compared with the raw material.…”
Section: Results Of Ftir Analysismentioning
confidence: 99%
“…8). The treatment was efficient because acid hydrolysis releases TMs in mobile forms [56], which presumably chelate readily with EDTA. The extended time of acid hydrolysis (1 h at pH 3) further increased the TMs removal efficiency to 91%-Pb, 73%-Zn, 3%-Cu, 63%-Mn, and 73%-Fe (Treatment No.…”
Section: Selection Of the Most Efficient Treatment To Remove Tms From Ssmentioning
confidence: 99%